Pyroptosis Modulators: New Insights of Gasdermins in Health and Disease - Imane Allali-Boumara; Ana Dácil Marrero; Ana R. Quesada; Beatriz Martínez-Poveda; Miguel Ángel Medina (MDPI AG, 2023)
Pyroptosis is an inflammation-dependent type of cell death that has been in the spotlight for the scientific community in the last few years. Crucial players in the process of pyroptosis are the members of the gasdermin family of proteins, which have been parallelly studied. Upon induction of pyroptosis, gasdermins suffer from structural changes leading to the formation of pores in the membrane that subsequently cause the release of pro-inflammatory contents. Recently, it has been discovered that oxidation plays a key role in the activation of certain gasdermins. Here, we review the current knowledge on pyroptosis and human gasdermins, focusing on the description of the different members of the family, their molecular structures, and their influence on health and disease directly or non-directly related to inflammation. Noteworthy, we have focused on the existing understanding of the role of this family of proteins in cancer, which could translate into novel promising strategies aimed at benefiting human health. In conclusion, the modulation of pyroptosis and gasdermins by natural and synthetic compounds through different mechanisms, including modification of the redox state of cells, has been proven effective and sets precedents for future therapeutic strategies.